Study the ability of rosemary leaf Ethanol extract to protect male rabbits’ liver and kidney against poisoning cypermethrin - Shireen Hasan; Ahlam Al-Rikaby (Basrah Journal of Veterinary Research)
Rosmarinus officinalis, L. (Lamiaceae) offers medicinal potential against hepatotoxicity and nephrotoxicity Due to its antioxidant and anti-toxicity properties. The objective, of this research is to explore into the ethanol extract of Rosmarinus officianalis leaves and its efficacy against  cypremethrin induce toxicity in The liver and  The kidney of male rabbits. Forty male rabbits were employed in this experience, group one ( without exposure); rabbits received corn oil ( 1 ml) group two; rabbits oral exposure to cypermethrin with dose (66.5 mg/kg/b.w ( 1/10 of LD50) dissolved in corn oil , group three( protective group) received rosemary extract with dose 100mg/kg plus cypermethrine with dose 66.5 mg/kg/b.w., group four received rosemary extract with dose 200mg/kg plus cypermethrine with dose 66.5 mg/kg/b.w. the above doses once per day for 6 weeks respectively.In accordance with the current study's findings, liver enzyme levels significantly increased. ALT,ALSand ALP),Lipid profile (TC,TG.LDL-cand VLDL_c) and  kidney function tests  (urea, a creatinine, uric acid and blood urea, nitrogen concentrations ) but significant decrease in (Total protein and HDL_ c value  ) in the treated group with cypermethrin , .whereas the animals received rosemary extract in both dose plus cypermethrin produced notable decrease in the  levels of the vital parameters of the liver and kidneys are with  the normal level. : the current study displayed that the Rosmarinus officinalis has antitoxicity activities as seen via decreasing liver enzymes, lipid profile and kidney function tests   is accompanied by elevated the levels of  total protein .